Potential of native Thai aromatic plant extracts in antiwrinkle body creams - Pimporn Leelapornpisid (2018)
© 2018 Society of Cosmetic Chemists. All Rights Reserved. Antioxidant activities of 10 essential oils and 10 absolutes extracted from Thai aromatic plants were evaluated and compared to thyme oil, trolox, quercetin, and kaempferol by two independent assays: the 2, 2-diphenyl-1-1-picrylhydrazyl (DPPH•) radical scavenging assay and the thiobarbituric acid reactive species (TBARS) assay for lipid peroxidation. We found that four essential oils including ginger oil (Zingiber officinale Roscoe), Wan-sao-long leaf oil (Amomum uliginosum Koen), lemongrass oil (Cymbopogon citratus), holy basil oil (Ocimum sanctum L.), and the absolute of dwarf ylang-ylang [Cananga odorata Hook. f. & Thomson var. fruticosa (Craib) J. Sinclair] exhibited high antioxidant activity in both DPPH and TBARS assays and possessed satisfactory fragrance properties. These were then combined into an essential oil blend (EOB) and retested for antioxidant activity. The EOB also exhibited high antioxidant activity in the above assays. It was then incorporated into a stable cream base as EOB body cream. The EOB body cream was found to be best able under storage in stress conditions and presented significantly higher antioxidant activity than its’ cream base both before and after stability testing. The effect of EOB body cream on skin surface topography was evaluated in 29 healthy volunteers using the Skin Visiometer®(SV 600 FW, CK Electronic GmbH, Germany). Three parameters, Ra, Rz (roughness), and surface, were analyzed. After 4 weeks of application, the EOB body cream showed significant reductions in surface and Rz compared with before treatment (p < 0.05, paired t-test), and with untreated and placebo treatment (p < 0.05, Duncan test). These results indicate that the essential oils and absolutes from Thai plants may serve as potential sources of natural antioxidants for spa and cosmetic products designed to prevent or treat signs of skin aging.